Perbandingan Performansi Sistem MC-SS Mimo dengan OFDM Mimo - Yuniari, Ni Putu Eka Apsari; Wirastuti, Ni Made Ary Esta Dewi; Hartawan, I G.A.K. Diafari Djuni (Majalah Ilmiah Teknologi Elektro; Vol 15 No 2 (2016): (July - December) Majalah Ilmiah Teknologi Elektro, 2016)
The combination of the system has been doing to improve the reliability of wireless communication. One parameter that indicates the reliability of wireless communication is to reduce the value of BER. The 4G technology uses OFDM transmission technique combined with MIMO antenna technique. Other than that, the combination between transmission technique can also be done, by incorporating the concept of multicarrier (OFDM) and spread spectrum as known as multicarrier spread spectrum (MC-SS). The combination of OFDM, spread spectrum, and MIMO are supported by the advantages of each of these techniques is expected to give a good performance in supporting the reliability of wireless communication. This research aimed to compare the value of BER vs. Eb/No between MC-SS MIMO system and OFDM MIMO system. The test of these systems are conducted by simulation using MatLab 2012 which aims to provide an overview of other related technologies are capable of providing wireless communication reliability.  The results of the simulation shows that the value of BER on MC-SS MIMO system is lower than MIMO OFDM system for all Eb/No. This condition also applies to AWGN and Rayleigh Fading channel.
Keywords: BER, Eb/No, Kehandalan, MIMO, OFDM, spread spectrum